Flexural Behaviour of Composite Beam-Column Connections - Khamail Abdul-Mahdi Mosheer, Mustafa B Dawood, M H Ghalib, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study includes an experimental investigations for the behavior of composite beam-column connections at static condition. The goals were to evaluate the effect of using cold-formed steel sections (CFS) which encasing in concrete as a replacement to steel bars of beam segment, while steel tube filled with concrete (CFST) used as column segment.. Results show an improve in cracking load, ultimate strength, and stiffness for composite specimens compared with specimen that using steel bars reinforcement under static condition